Travel demand management options in Beijing. (Metro Manila, Philippines Asian Development Bank, 2017)
Rapid urbanization and motorization combined with high population density have led to serious congestion and air quality problems in the Peoples Republic of China capital of Beijing. While Beijing accounts for less than 2% of the population, more than 10% of the countrys vehicles ply the citys roads. This study is part of the Asian Development Banks initiative to support greener and more sustainable transport systems that are convenient and lessen carbon dioxide emissions. Read how congestion charging, vehicle ownership quotas, and progressive parking reforms can improve Beijings approach to travel demand management.
Keywords: Transportation and state -- Beijing,China; Energy policy -- Beijing,China; Electronic books